Rancang Bangun Mesin Pengepres Sandal Mengunakan Roll Kapasitas 60 Buah/Menit dengan Daya Motor 1 HP - Trio Setiyawan; Hening Krisna Adi; Satrio Erdiano; Syahru Romadlon Fanani; Mohammad Samsul Bakhri (Politeknik Negeri Semarang, 2023)
Abstract Sandals are a need for clothing for humans which are often used in daily activities, sandals are also protective feet for humans when on the move. Sandals have several types, in this study the authors focused on sandals made of EVA sponge. In the process of making sandals, several machines or tools are needed to make sandals, while this research will focus on the sandal adhesive machine. The purpose of this research is to get perfect gluing results in making sandals using a roll machine which is easy to operate and maintain. The method used is gluing the sandal material through a rolling process which is carried out by placing the sandal material on the guide table, then the sandal material is entered between a pair of pulling rolls and then forwarded to the next pair of rolls for the gluing or pressing process. The end result of the design of this sandal pressing machine can produce sandals production capacity of up to 60 sandals/minute with a shear stress strength of 0.1505 N/mm².